Implementation of the Open Defecation Free Study Program in Sungai Dua Village Rambutan District Banyuasin Regency - Juniarti, Vivi Rizky; Siswanto, Joko (HM Publisher, 2019)
This research is motivated by the fact that there are still many Latrine Villagers who do not comply with Community-Based Total Sanitation Criteria. This study aims to determine the implementation of the Open Defecation Free Program in Sungai Dua Village, Rambutan District, Banyuasin Regency. This research uses descriptive qualitative research methods with the type of descriptive research. The type of data used is primary data and secondary data. Data collection techniques are done through observation, in-depth interviews and documentation. This study uses the Policy Implementation Theory of Ripley and Franklin, where the success of policy implementation is influenced by three dimensions namely (1) the level of compliance, (2) the smoothness of routine routines and (3) the desired performance and implementation impact. Based on the results of field research, it shows that the level of compliance in the implementation of the program is not yet optimal, the smoothness of routine functions has not run smoothly, and the desired performance and impact of implementation have not been maximized and not yet achieved. The conclusion of this research is that the implementation of the Open Defecation Free Program in Sungai Dua Village, Rambutan District, Banyuasin Regency has not been successful. This research suggests that all rules are obeyed and implemented, it is necessary to increase monitoring and coordination on a regular basis.